Struktur Kalimat Perbandingan Berpemarkah -you Bermakna Menyatakan Kesamaan sebagai Reiji (例示) dan Hikyou (比況) - Nani Sunarni (Faculty of Letters, Dr. Soetomo University, 2022)
This research is within the scope of syntactic studies, focused on the study of comparative sentences marked with -you which express similarities by showing examples or reiji (例示) and which express similarities through comparisons or parables with something or hikyou (比況). The data used are comparative sentences sourced from Manabou Nihongo Shochuukyuu's book (Igari Miho et al., 2006) and self-made sentences (sakurei). The method of this study is a qualitative descriptive method. The sentence pattern mentioned first consists of has five patterns, namely 「V youni V」,「N no youni V」, 「N no youni A」,「V/N no youna N」,「 N no you (da)」. And the second mentioned sentence pattern has two patterns, namely 「N no youna N」and 「N no youni V (A)」. The 「V youni V」 pattern expresses the similarity meaning of the activity. The pattern 「N no youni V」expresses the meaning of similarity related to the activity of a person or object that is a concrete example. The pattern 「N no youni A」 expresses the meaning of the similarity of a condition or nature contained in a person or an object. The pattern 「V/N no youna N」 expresses the meaning of stating the similarity related to the activity or resemblance to an object being exemplified. The pattern 「N no you (da)」 means to express the similarity between an object and the object being exemplified. Then, the pattern 「N no youna N」 states the meaning of resemblance to the comparison between objects and objects. Meanwhile, the pattern 「N no youni V(A)」 expresses the meaning of similarity through comparisons expressed by verbs or adjectives with nouns. This study can be used as teaching material for understanding comparative sentences in Japanese. Keywords: comparison sentences; hikyou; reiji; -you